TRADING ON EQUITY: AN ALTERNATIVE SOURCE OF CAPITAL STRUCTURE - Srivastava, Surbhi; Kumar Singhal, Prof. Ajai (IJRDO - Journal of Business Management, 2016)
The capital structure decision is a key factor in the success of the firm. There is no unique formula that solves a firm’s capital structure allocation, nor is there likely to be one. However, a careful study of the field should enable individuals to specify appropriate boundaries of how much of each type of financing is reasonable and required as it is necessary for a firm to evaluate the various sources of capital to attain the optimal capital structure, therefore this article discusses some of the features of trading on equity as an alternative source of capital structure with implications.